Socio-environmental indicators as subsidy to the prevention and control of Dengue - Feitosa, Flávia Regina Sobral; Sobral, Ivana Silva; Jesus, Edilma Nunes de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This work aimed to select environmental, economic and social indicators to assist the municipal health management of Aracaju to redirect the look on his care of territory, more participatory and integrated, according to the wider definition of health. The study area were two districts of the municipality said: Jabotiana and New Town. The theoretical and methodological design used was the ecosystem approach, by covering the dimensions, environmental, economic, political and social. This is a descriptive qualitative study, conducted through thecollection and analysis of bibliographic and documentary data. The indicators were selected based on the methodology Pressure -State -Impact / Effect -Response (PEI / ER) model-based Pressure / State / Response (PER) of the Organization for Economic Cooperation and Development (WINOGRAD,1996). Added to selected indicators, forward-looking indicators, which consist in proposing actions that may assist the administration in the presented problem. Thus, twenty-six indicators was generated, which could serve as a tool for planning the actions of epidemiological surveillance. It is hoped that this study may support the assessment of the causes and incidence of effects of this disease and may contribute in public policies for the prevention and control of Aedes aegypti.